The Influence of Formal and Informal Ethical Systems on Employees’ Unethical Decisions - Clara Koetz; Sarah Hudson (M@n@gement)
This paper examines the effect of formal (e.g., codes of conduct [COC] and punishment) and informal (e.g., peer behavior) ethical systems on employees’ unethical intentions. Previous studies disagree about the effectiveness of COC and punishment policies on individuals’ unethical intentions. Moreover, there is not much research regarding the interactive effects of formal and informal norms in organizations on unethical behavior and how employees decide when there is incongruence between formal and informal ethical systems. To investigate this, we propose the following research question: What is the effect of distinct formal (implicit and explicit COC and strong and weak punishment policies) and informal (peers’ ethical and unethical behaviors) ethical systems on individuals’ unethical decisions? The results of an exploratory qualitative study (N = 275) and an experimental study (N = 374) demonstrate that (1) peer behavior has the strongest effect on individuals’ unethical intentions; (2) punishment and clear COC combined are effective in reducing unethical intentions when peers behave unethically; however, in these contexts, rules are ineffective when not supported by punishment policies, and punishment can be counterproductive when rules are implicit or nonexistent. Our study contributes to the literature on ethical decision-making by showing how combinations of formal and informal ethical systems influence unethical intentions. It also offers valuable recommendations to managers on reducing unethical behavior in companies.